Relationship between Exercise Addiction, Orthorexia Nervosa, and Sports Supplement Attitude in Turkish Fitness Participants - Özgen, Caner; Köse, Hüseyin; Reyhan, Servet (Progress in Nutrition, 2022)
Study Objectives: There is not enough evidence in the literature for a causal relationship between ON, which is generally expressed as an obsession with healthy eating, and EA, which is expressed as an individual’s loss of control over exercise behavior. The aim of this research is to determine the causal relationships between ON, EA, and SSA (Sports Supplement Attitude) in individuals who do fitness. Method: Within the scope of the research, 204 people who are doing fitness were reached by convenience sampling method. The obtained data were analyzed within the scope of structural equation modeling. Results: As a result, of the analyzes of the hypotheses put forward within the scope of the structural model, it has been determined that EA is an important antecedent of ON within the scope of individuals doing fitness. While it has been empirically proven that SSA is an important precursor of EA, ON has no significant effect on SSA. Conclusion: The results revealed that ON behavior is not only related to maintaining a healthy lifestyle, but also has aesthetic concerns within the scope of individuals who do fitness. In addition, the significant positive effect of SSA on EA is an important evidence among the risks that affect the formation of EA behavior. Finally, the finding that ON has no significant effect on SSA has opened the door to new research that will point to the difference between ON and other eating disorders.